Limits on quality of life in communication after total laryngectomy - Chaves, Adriana Di Donato; Pernambuco, Leandro de Araújo; Balata, Patrícia Maria Mendes; Santos, Veridiana da Silva; de Lima, Leilane Maria; de Souza, Síntia Ribeiro; da Silva, Hilton Justino (International Archives of Otorhinolaryngology, 2012)
Introduction: Among people affected by cancer, the impairment of quality of life of people affected by cancer can cause have devastating effects. The self-image of patients after post-laryngectomyzed patients may be find themselves compromised, affecting the quality of life in this population.Objective: To characterize quality of life in related to communication in people who have undergone went total laryngectomy surgery.Methods: This is an observational study, with a cross-sectional and descriptive series.Design of series study. The sample were comprised 15 patients interviewed the period from January to February of 2011. We used the Quality Protocol for Life Communication in Post-laryngectomy adapted from Bertocello (2004); which this questionnaire contains 55 questions. The protocol was organized from the nature of using responses classified as positive and negative aspects, proposals in with respect to five 5 communication domains: family relationships, social relationships, personal analysis; morphofunctional aspect, and use of writing. To promote and guarantee the autonomy of the respondents, was examiners made use of used assistive technology with the Visual Response Scale.Results: The responses that total laryngectomy compromises the quality of life in communication amounted to 463 occurrences (65.7%), and that who responses suggesting good quality of life were represented with amounted to 242 occurrences (34.3%), from a total of 705 occurrencesresponses. From Among the five 5 Communication domains, four 4 had percentages of above 63% for occurrences of negative content for impact on communication. Appearance Morphofunctional appearance gave the had the highest percentage of negative content, amounting to 77.3% of cases.Conclusions: The results showed important limitations of a personal and social nature due to poor communication with their peers. Thus, there is a need for multidisciplinary interventions that aim to minimize the entrapment of negative impact on these people communication among these patients.
Keywords: quality of life; laryngectomy; communication; protocols